A review of distribution and diversity of butterfly (Lepidoptera: Rhopalocera) fauna in Johor, Malaysia - Aqilah Awg Abdul Rahman,; Maryati Mohamed,; Norradihah Ismail,; Noor Izwan Anas, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
The objectives of this paper are to (i) review the diversity and distribution of butterflies in different forested areas of Johor and (ii) compare the species composition in each study site. Data is based on field sampling and published records. This paper was able to review study sites from records dating as early as 1987. Study sites include Taman Negara Johor Endau Rompin (TNJER) Peta, TNJER Selai, Gunung Ledang, Bukit Reban Kambing, Bukit Soga and Hutan Lipur Sg Bantang. To evaluate the variation in butterfly diversity in the different forest, the study sites were characterized by describing and comparing overlapping species using hierarchical cluster analysis. To date, a total of 396 species of butterflies are recorded so far in Johor. This accounts for 37.57% of the overall butterfly fauna in Peninsular Malaysia. The highest species richness was recorded in TNJER with a total of 349 species discovered to date. Based on the cluster analysis, species composition in TNJER Peta and Selai showed the highest similarity at 37%. Locality with the most different species composition was Bukit Tukau, Bukit Belading and Bukit Reban Kambing with only 7% similarity. Remarkably, many of the protected species under Wildlife Conservation Act 2010 can be found in Johor. These species include Zeuxidia aurelius aurelius (Cramer), Polyura eudamippus peninsularis (Pendlebury), and Troides helena cerberus (C. & R. Felder). Data obtained from this paper is important for future planning and management of conservation areas in Johor.